Body weight, body condition score and heart girth in indigenous Tswana goats during the dry and wet seasons in southeast Botswana - Nsoso,S.J.; Aganga, A.A.; Moganetsi, B.P.; Tshwenyane, S.O. (2003)
Body condition scoring (BCS) is a simple and easy technique, which allows subjective assessment of an animal’s body composition to help in adopting appropriate management strategy. Information on BCS is not available for indigenous Tswana goats. The aims of this study were to establish the relationships among body weight, body condition score and heart girth in indigenous Tswana goats raised under extensive and semi-intensive management during the dry and wet seasons in southeast Botswana. A total of 100 indigenous Tswana goats, owned by farmers and managed extensively, in wet and dry seasons, were used in Experiment 1; while 50 mature indigenous Tswana goats from the Botswana College of Agriculture were used in Experiment 2 in the dry season only under semi-intensive management. In both experiments, data were collected fortnightly on body weight, body condition score and heart girth for 12-20 weeks. Season significantly affected BCS, with lower scores (2.17±0.10 to 2.65±0.10) in the dry season than in the wet season (3.17±0.10 to 3.79±0.11), but has no effect on body weight or heart girth. Management did not significantly affect body condition score. There was no apparent relationship between body weight and condition score. Body weight was closely correlated with heart girth under extensive management in the wet season but not in the dry season. It is concluded that BCS is a more useful indicator of seasonal nutritional effects in goats than body weight or heart girth.